Digital Strategic Initiatives and Digital Resources: Construct Definition and Future Research Directions - Piccoli, Gabriele; Rodriguez, Joaquin; Grover, Varun (MIS Quarterly, 2022)
This paper explores the structure and design of digital strategic initiatives (DSI): identifiable competitive moves that depend on digital resources to create and appropriate economic value. We use the term digital deliberately, in line with the recent push for discerning the so-called IT “x” and Digital “x” phenomena. The paper contributes to basic science by precisely defining the digital strategic initiative concept and its essential elements: digital resources. It clarifies the difference between digital resources and established constructs such as IT resources and IT-enabled resources. We posit that the defining characteristics of digital resources are their modular design, encapsulation of value, and programmatic interface. This work also shows how the design and development of digital strategic initiatives thrive in an infrastructural, combinatorial, and servitized environment. Using illustrative cases, we demonstrate applications of the concepts by introducing two value creation pathways for DSI: (1) orchestration of digital resources and (2) creation of novel digital resources. The paper concludes by presenting open research questions and offering extensions for future inquiry.